Cartilage Regeneration Characteristics of Human and Goat Auricular Chondrocytes - Hou, Mengjie; Bai, Baoshuai; Tian, Baoxing; Ci, Zheng; Liu, Yu; Zhou, Guangdong; Cao, Yilin (Frontiers in Bioengineering and Biotechnology, 2021)
Although cartilage regeneration technology has achieved clinical breakthroughs, whether auricular chondrocytes (AUCs) represent optimal seed cells to achieve stable cartilage regeneration is not clear. In this study, we systematically explore biological behaviors of human- and goat-derived AUCs during in vitro expansion as well as cartilage regeneration in vitro and in vivo. To eliminate material interference, a cell sheet model was used to evaluate the feasibility of dedifferentiated AUCs to re-differentiate and regenerate cartilage in vitro and in vivo. We found that the dedifferentiated AUCs could re-differentiate and regenerate cartilage sheets under the chondrogenic medium system, and the generated chondrocyte sheets gradually matured with increased in vitro culture time (2, 4, and 8 weeks). After the implantation of cartilage sheets with different in vitro culture times in nude mice, optimal neocartilage was formed in the group with 2 weeks in vitro cultivation. After in vivo implantation, ossification only occurred in the group with goat-regenerated cartilage sheet of 8 weeks in vitro cultivation. These results, which were confirmed in human and goat AUCs, suggest that AUCs are ideal seed cells for the clinical translation of cartilage regeneration under the appropriate culture system and culture condition.